RFreeTrack: RFID non-contact robust positioning system based on differential phase holography - Linqing GUI; Yi JIANG; Qingyun ZHANG; Fu XIAO (Tongxin xuebao)
To address the issue of large positioning errors in complex environments within non-contact RFID-based positioning systems, RFreeTrack system was proposed.Commercial RFID equipment was used to calculate the reflected signals from targets, achieving high-precision non-contact positioning in complex environment.Firstly, a search method based on time-series similarity was proposed to employ for calibrating static signals, thus significantly enhanced the robustness of target reflection signal extraction.Secondly, a non-contact positioning method based on differential phase holography was introduced to eliminate the influence of the reader antenna’s position, thus the accuracy of positioning was improved and the complexity of system was deployment reduced as well.Finally, a high-precision non-contact positioning system prototype was realized.Experimental results indicate that in complex environments, the phase of the target reflection signals extracted using the calibrated static signals has a 68.8% lower error compared to existing methods.Based on the previously calibrated static reflection signals, the average positioning error using differential phase holography in complex environments is 0.040 8 m, and has a 50.6% improvement on location over existing methods.